Chapter Career Calling: Lights and Shadows - Startari, Sonia (Studies on Adult Learning and Education, 2018)
In this moment the policies on lifelong guidance, recognition of learning and skills certification seem more working on who should do what and not on how make. It would be desirable to create links between the various providers of training, education and business, allowing for a reframing of orientation processes and of identification and certification of skills. All these practices can reduce distances for those who are likely to remain at the margins of education, training and work (Neet and over fifty)